Unplanned pregnancy on a direct oral anticoagulant (Rivaroxaban): A warning. (March 2016) - Myers, B; Neal, R; Myers, O; Ruparelia, M
Direct oral anticoagulants (DOACs or NOACs -non-vitamin K oral anticoagulants), as the name suggests, are oral anticoagulants with a direct inhibitory action either against factor X or factor II (thrombin). Pregnant women were excluded from participating in all the large trials of the DOACs and they are considered contra-indicated in pregnancy and breast feeding. We present a case of inadvertent exposure to rivaroxaban in a woman who presented at 25 weeks' gestation. The management of her pregnancy and delivery is described, and the previous published case reports are reviewed with a discussion about the use of DOACs in woman of childbearing age.